Seleksi Pohon Teduhan di Kampus Universitas Lambung Mangkurat Banjarbaru - Nova Annisa; Krisdianto Krisdianto; Setia Budi Peran (Bioscientiae, 2020)
This study aims to determine the type of tree, number of stomata, the proportion of canopy closure and water content in the leaves of several types of shade trees located on the campus of ULM Banjarbaru, and the relationship between the number of leaf stomata to leaf area, if there is a proportion factor thought to affect the water content will be controlled. Data obtained in the analysis of the proportion of water content in the leaves, the proportion of canopy closure, the location of the tree, and the number of stomata by using descriptive analysis and digital image analysis of satellite data. To determine the relationship between leaf area, the proportion of canopy closure and water content in the leaves of the shade trees used partial correlation analysis with SPSS version 17. Based on the results of a study of the density of stomata in the size of 1 cmÂ², found 10 species of trees shade the best such as Psidium guajava (guava), Mangifera casturi (kasturi), Hevea brasiliensis (rubber), Pithecellobium lobatum (jengkol), Mangifera indica (mango), Theobroma cacao (brown), Persea americana (avocado), Eugenia aquea (rose apple), Gnetum gnemon (melinjo), and Arthocarpus heterophyllus (jackfruit). The density of leaf stomata are not related to the broad leaves of the shade tree on the campus ofÂ  ULM Banjarbaru.